2018
DOI: 10.1016/j.resuscitation.2017.11.058
|View full text |Cite
|
Sign up to set email alerts
|

‘ She’s sort of breathing ’: What linguistic factors determine call-taker recognition of agonal breathing in emergency calls for cardiac arrest?

Abstract: There is potential for improved recognition of agonal breathing if call-takers are trained to be alert to any qualification following a confirmation that the patient is breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 29 publications
0
33
0
5
Order By: Relevance
“…Recent research has explored the impact of call-takers’ linguistic choices on the efficiency of ambulance dispatch in high-acuity cases, including cardiac arrests, 17 and in the detection of agonal breathing. 18 Earlier work has long recognised the communication challenges posed by the pressure of these ‘high-acuity’ and ‘high-stakes’ situations, 19 and on-going research confirms the importance of a more detailed understanding of the dynamics between caller and call-taker to improve dispatch efficiency in these circumstances (eg, refs 17 20 ). However, little work has been undertaken to explore emergency call interactions in lower-acuity situations, such as for ‘primary care sensitive’ problems.…”
Section: Introductionmentioning
confidence: 94%
“…Recent research has explored the impact of call-takers’ linguistic choices on the efficiency of ambulance dispatch in high-acuity cases, including cardiac arrests, 17 and in the detection of agonal breathing. 18 Earlier work has long recognised the communication challenges posed by the pressure of these ‘high-acuity’ and ‘high-stakes’ situations, 19 and on-going research confirms the importance of a more detailed understanding of the dynamics between caller and call-taker to improve dispatch efficiency in these circumstances (eg, refs 17 20 ). However, little work has been undertaken to explore emergency call interactions in lower-acuity situations, such as for ‘primary care sensitive’ problems.…”
Section: Introductionmentioning
confidence: 94%
“…Prompt action by bystanders can help to 'buy time' until more definitive treatment is available by the ambulance paramedics, and bystander CPR in this period more than doubles the chance of survival [36,37], with differences in the rates, interventions, and survival in different regions [38]. The training of takers of emergency ambulance calls also has the potential to improve bystander contributions to survival [39].…”
Section: Importance Of Delays In Acute Coronary Syndromementioning
confidence: 99%
“…Bezüglich der DA-CPR sei hier beispielhaft auf die Frage „Atmet die Person normal?“ eingegangen, um zu zeigen, wie Schulung auf die Leistung der Notrufexperten Einfluss nehmen kann. In einer englischsprachigen Studie von Riou [ 15 ] wurden Anrufe mit rückgemeldeten OHCA durch die Einsatzkräfte vor Ort analysiert. Der Fokus lag auf sprachlichen Faktoren der Beantwortung der Frage „Atmet der Patient normal?“ durch den Anrufer.…”
Section: Telefonreanimationunclassified
“…Begründungen für die „Ja, aber“-Antworten findet Riou im Übrigen im sprachlichen Kontext wissenschaftlicher Untersuchungen. „Research on spontaneous conversation has identified a social preference for confirming answers to questions“ ([ 15 ]; deutsche Übersetzung: „Studien zu spontanen Gesprächen zeigen eine soziale Tendenz, auf Fragen bestätigend zu antworten“). Auf den Notrufdialog bezogen tendieren Ersthelfer mit Zweifel, „ob der Patient atmet oder nicht“, dazu, bejahend beschreibend zu antworten, beispielsweise mit „Ja, aber er/sie keucht/schnarcht“.…”
Section: Telefonreanimationunclassified